Polyprotein Precursors to Mouse Mammary Tumor Virus Proteins - Anderson, S. J. (1979)
Mouse mammary tumor virus (MMTV) derived from the culture medium of GR cells contained seven proteins, identified as gp55, gp33, p25, pp20, p16, p12, and p10. The major viral phosphoprotein was the 20,000-molecular-weight protein, pp20. Immunoprecipitation of cytoplasmic extracts from pulse-labeled GR cells identified three MMTV gag-specific proteins, termed Pr78(gag), Pr110(gag), and Pr180(gag+). These intracellular polyproteins were precipitable from cytoplasmic extracts by antisera to virions p25 and p12 but not by antisera to gp55. The major intracellular gag-specific precursor polyprotein, Pr78(gag), contained antigenic determinants and tryptic peptides characteristic of p25, p12, p10, and presumably pp20. This precursor is presumably derived from nascent chain cleavage or rapid posttranslational cleavage of the larger intracellular precursor-like protein, designated Pr110(gag). Pr110(gag) contained all but one of the leucine-containing tryptic peptides of Pr78(gag), plus several additional peptides. In addition to Pr78(gag) and Pr110(gag), monospecific antisera to virion p12 and p25 were also capable of precipitating from pulse-labeled cells a small amount of a 180,000-molecular-weight precursor-like protein, designated Pr180(gag+). This large polyprotein contained nearly all of the leucine-containing tryptic peptides of Pr78(gag) and Pr110(gag) plus several additional peptides. By analogy to type C viral systems, Pr180(gag+) is presumed to represent a gag-pol common precursor which is the major pathway for synthesis of MMTV polymerase. Immunoprecipitation of cytoplasmic extracts from pulse-labeled cells with antisera to gp55 identified two env-specific proteins, designated gPr76(env) and gP79(env). The major env precursor, gPr76(env), could be labeled with radioactive glucosamine and was shown to contain antigenic determinants and tryptic peptides characteristic of gp55 and gp33. A minor glycoprotein, gP79(env), contained both fucose and glucosamine and was precipitable from cytoplasmic extracts with monospecific serum to gp55. It is suggested that gP79(env) represents fucosylated gPr76(env) which is transiently synthesized and cleaved rapidly into gp55 and gp33.